Hidroformilação de monoterpenos para-mentênicos catalisada por complexos de ródio - Camila Grossi Vieira (2009)
This paper reports the results on the rhodium catalyzed hydroformylation of terpinolene under milder reaction conditions and in the presence of a phosphorous ligand. An appropriate choice of these conditions allows a relatively rapid hydroformylation of the substrate with a combined selectivity for three main aldehydes of up to 85% at 90% conversion. The mixture of these aldehydes can be used in fragrance compositions due to its pleasant organoleptic properties. The aldehydes were identified and characterized by GC-MS, NMR of 1H, of 13C, DEPT, NOESY, COSY and HMQC. The results indicate that the hydroformylation of the endocyclic double bond in terpinolene is only possible because of the special properties of tris(o-tercbutylphenyl)phosphite. Due to the large cone angle of this ligand, catalytically active monoligand rhodium species predominate in the reaction solutions even at high P/Rh ratios allowing the coordination of the sterically encumbered olefin. Much more modest results were found when PPh3 was used as an auxiliary ligand under the same reaction conditions